Faktor-Faktor Yang Mempengaruhi Minat Ibu Menggunakan KB AKDR di PMB Nuri Utamining Depok - Barus, Maghdalena; Elisabet Br Ginting, Linda (Universitas Haji Sumatera Utara, 2024)
The author polled ten women who had expressed an interest in family planning at PMB Nuri Utamining with five questions; five of the women said they were familiar with intrauterine devices (IUDs) but had no plans to use them, three said they knew very little about them and were also uninterested, and two said they were both knowledgeable about IUDs and would like to use them. This study falls under the category of analytical observational research since it does not treat research subjects in any way to help researchers understand the issue more thoroughly. This study used a cross-sectional design and was a survey in nature. Mothers who enrolled in the family planning program at PMB Nuri Utamining in Depok made up the study's population. After using the Slovin algorithm to the process of sample selection, a total of 45 respondents were selected for this investigation. We employed a sequential sampling technique. It has been determined through research and discussion that the following relationships exist: Education (p = 0.043), Knowledge (p = 0.001), Socio-Culture (p = 0.006), Husband's Support (p = 0.002), and Parity with Mother's Interest in Using IUDs at PMB Nuri Utamining (p = 0.009). The goal of the educational activities planned by PMB Nuri Utamining and local health centers is to raise awareness among PUS about the merits of intrauterine device (IUD) KB use, which should pique their interest in trying it out and encourage them to actively seek out more information about it.